Post-Sekularisme, Demokrasi, dan Peran Publik Agama - Petrus Tan (Institut Filsafat dan Teknologi Kreatif Ledalero, 2021)
This article tries to elaborate the relationship between post-secularism, democracy and the public role of religion. The facts of religion’s global revival show the failure of secularization thesis about the disappearance of religion from the public sphere. In political philosophy and social sciences, this phenomenon is called post-secularism. In this article, post-secularism is understood as a phenomenon of religion’s revival in the public sphere or the legitimacy for public role of religion. This understanding is especially necessary to encourage religion in addressing political, social and humanitarian issues. However, this understanding does not ignore the fact that religion often becomes a scandal and terror for democracy. Therefore, in this article, post-secularism also needs another understanding, namely as